Sexual behavior of elderly people and their vulnerabilities to sexually transmitted infections (Research, Society and Development, 2020)
Objectives: to describe the sexual practices of elderly males and discuss their vulnerabilities to Sexually Transmitted Infections. Methodology: a descriptive, exploratory study with a qualitative approach developed in a university hospital in the city of Rio de Janeiro with 30 elderly people from November 2018 to January 2019, through semi-structured interview. The data were analyzed using the content analysis technique. Results and Discussion: The analysis pointed out 2 categories: The sexual practices of the elderly and Vulnerabilities of the elderly to sexually transmitted infections. It was found that, although the elderly have sexually active lives, there is a gap in knowledge about transmission and prevention strategies for sexually transmitted infections. This lack of knowledge increases the individual vulnerability that is referred to, information and protective behaviors or practices, highlighting the behavioral and rational bias, anchored in intersubjective relationships. Final Considerations: It becomes relevant to establish health education actions for the elderly, aimed at incorporating a safe sexual practice, based on demystifying information, regarding the training of nursing professionals, seeking to deconstruct the culture that sexual practice is not. performed in the elderly.